2018
DOI: 10.1177/0300060518808179
|View full text |Cite
|
Sign up to set email alerts
|

Congenital tuberculosis after in vitro fertilization: suggestion for tuberculosis tests in infertile women in developing countries

Abstract: Congenital tuberculosis (CTB) after in vitro fertilization (IVF) is a major new problem in developing countries. Only 16 cases of CTB after IVF have been reported, and no tuberculosis (TB) tests were performed before IVF in these cases. However, on the basis of data in the literature and from the World Health Organization, the incidence of CTB has been substantially underestimated. We describe two cases of CTB after IVF in detail in our center and provide new insight into the important issue of controlling TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Postnatal, one baby was reported with congenital TB. Similar cases with congenital TB after IVF-ET have been reported before ( Zhang et al., 2018 ). The TB screening before IVF-ET is essential to decreasing the prevalence of congenital TB in neonates.…”
Section: Discussionsupporting
confidence: 87%
“…Postnatal, one baby was reported with congenital TB. Similar cases with congenital TB after IVF-ET have been reported before ( Zhang et al., 2018 ). The TB screening before IVF-ET is essential to decreasing the prevalence of congenital TB in neonates.…”
Section: Discussionsupporting
confidence: 87%
“…A Chinese study by Zhang et al reported two women with TB successfully conceived via in vitro fertilization (IVF); however, both of their babies died 56 days after the birth due to respiratory disorders with one infant confirmed with the diagnosis of TB. Not surprisingly, TB screenings were not prescribed in both of the mothers before the initiation of IVF [ 17 ]. Therefore, considering the potential deleterious maternal and neonatal outcomes of women with TB if passed undiagnosed, the high prevalence of TB in China, and the enormous number of Chinese women receiving infertility care every year, we strongly propose that TB screening should be mandated for all women seeking infertility evaluation and treatment in China.…”
Section: Discussionmentioning
confidence: 99%
“…Possible risk factors for congenital TB are as follows: (1) Infants born to mothers who have primary TB, which often has a haematogenous (bacillaemic) phase (see Clinical presentation) (6), (2) mothers co-infected with TB and HIV, and (3) mothers who had undergone in vitro fertilization (IVF) with TB as the cause of infertility (13).…”
Section: Epidemiologymentioning
confidence: 99%
“…TB of the genitourinary tract is a common cause of infertility; several cases of congenital TB were reported in infants of mothers who had undergone IVF; therefore, TB should be excluded and treated before IVF is performed to prevent congenital TB in their infants (13).…”
Section: Prevention Of Tb In Mothers and Their Infantsmentioning
confidence: 99%
See 1 more Smart Citation